From Stents to Smart Implants Employing Biomimetic Materials: The Impact of 4D Printing on Modern Healthcare - Antreas Kantaros; Florian Ion Tiberiu Petrescu; Theodore Ganetsos (Biomimetics)
The sector of 4D printing represents a new frontier in additive manufacturing that allows for a material’s capability to adapt and respond to various stimuli, such as thermal transitions, humidity, and pH levels. The adaptability of such a material has great potential in healthcare applications, especially in designing personalized and responsive medical devices. This article looks into the revolutionary potential of healthcare applications of 4D printing, referencing applications in self-repairable implants, smart stents, personalized drug delivery systems, and response-based prosthetic devices. The advances in 3D printing have created a platform for such innovations to take place, while the material properties unique to 4D printing allow new methods of tackling existing health issues. However, the large-scale application of 4D printing in medicine is currently hampered by material limitations, regulation challenges, and financial challenges. In spite of these challenges, ongoing advances in technologies, combined with artificial intelligence and machine learning, provide the potential to surpass such challenges, hence improving the precision, efficacy, and personalization of medical devices. This work outlines existing applications, looks at potential areas of application in the future, and analyzes potential applications of 4D printing contributing to healthcare, recognizing challenges that need to be overcome in order to unlock its full potential.